A review on the rotary ultrasonic machining of advanced ceramics - Khoo, C. Y.; Hamzah, Esah; Sudin, Izman (Faculty of Mechanical Engineering, 2008)
Advanced ceramics are likely candidates for many industrial applications due to their superior properties. However, their high machining costs lead to limited applications. Rotary ultrasonic machining (RUM) is one of the cost-effective machining processes available for drilling holes in advanced ceramics. This paper reports on investigations in the last few years on RUM process of advanced ceramics. Emphasis is given on the effect of RUM process parameters (such as applied static load, rotational speed, ultrasonic power and vibration amplitude, abrasive grit size and coolant) on machinability parameters (such as material removal rate, tool wear and surface roughness). Results on tool wear and edge chipping are also reported.